2016
DOI: 10.1088/1009-0630/18/3/09
|View full text |Cite
|
Sign up to set email alerts
|

Microwaves Scattering by Underdense Inhomogeneous Plasma Column

Abstract: The scattering characteristics of microwaves (MWs) by an underdense inhomogeneous plasma column have been investigated. The plasma column is generated by hollow cathode discharge (HCD) in a glass tube filled with low pressure argon. The plasma density in the column can be varied by adjusting the discharge current. The scattering power of X-band MWs by the column is measured at different discharge currents and receiving angles. The results show that the column can affect the properties of scattering wave signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There have been several studies [1,2,4] on plasma as the microwave reflector or the absorber based on its application in the field of RADAR communication. Shen et al observed that plasma with density above n ≥ 1.2 × 10 18 m −3 , produced by using low ionisation energy organic gas microwaves of X-band can be absorbed [6]. A similar study has been carried out by Zhang and Scharer, where plasma was generated using low ionisation potential gas such as tetrakis (dimethylamino) ethylene (TMAE) [7,8].…”
Section: Introductionmentioning
confidence: 82%
“…There have been several studies [1,2,4] on plasma as the microwave reflector or the absorber based on its application in the field of RADAR communication. Shen et al observed that plasma with density above n ≥ 1.2 × 10 18 m −3 , produced by using low ionisation energy organic gas microwaves of X-band can be absorbed [6]. A similar study has been carried out by Zhang and Scharer, where plasma was generated using low ionisation potential gas such as tetrakis (dimethylamino) ethylene (TMAE) [7,8].…”
Section: Introductionmentioning
confidence: 82%
“…cylindrical plasma. Moreover, in addition to collision absorption, the columnar plasma also enables electromagnetic wave scattering to further reduce reflections [27,28]. Hence, the design is made by placing several mutually parallel cylindrical plasmas in the plane where the hyperplane is located.…”
Section: Simulation and Experimentation Of Structures Formed By The C...mentioning
confidence: 99%
“…To analyse the optical characteristics of the EM wave, the reflection and transmission coefficients are introduced as an absolute square of Equations ( 16) and (17). Considering expressions of the reflection and transmission amplitudes and using Equations ( 6) and ( 18), the reflection and transmission coefficients of the EM wave can be derived as…”
Section: Physical Model Of Wave Propagation In Bounded Plasmamentioning
confidence: 99%
“…[10][11][12] Microwave scattering from homogeneous and inhomogeneous plasma was studied in detail by Laroussi, Shi, Helaly, and others. [13][14][15][16][17] The scattering matrix method (SMM) is widely used to investigate EM wave propagation in multilayer, non-uniform, magnetized, and unmagnetized plasma slabs. [18][19][20][21][22] Theoretical and numerical methods such as finite-difference time-domain (FDTD), finite difference frequency domain (FDFD), impedance matching (IM), and Green's function volume integral (GFVI) were introduced and recently were developed to simulate propagation characteristics of wide ranges of EM wave in different types of bounded plasmas.…”
Section: Introductionmentioning
confidence: 99%